Effectiveness of a training course for general practice nurses in motivation support in type 2 diabetes care: a cluster-randomised trial. - Lise Juul; Helle T Maindal; Vibeke Zoffmann; Morten Frydenberg; Annelli Sandbaek (PLoS ONE)
Background Type 2 diabetes is a common metabolic disease with the potential for prevention of complications. The prevention requires a high level of lasting actions from the patients, which may be burdensome. The aim of this trial was to evaluate the effectiveness of a training course for general practice nurses in motivation support at 18 months follow-up in the affiliated type 2 diabetes population. Methods Forty general practices with nurse-led diabetes consultations from the area of Aarhus, Denmark were randomised 1∶1 to either intervention or usual practice. Intervention practices were offered a 16-hour Self-determination theory-based course including communication training for general practice nurses delivered over 10 months. The affiliated diabetes populations (aged 40-74 years) were identified from registers (intervention n = 2,005; usual n = 2,029). Primary outcomes were register-based glycated haemoglobin (HbA1c) -, total cholesterol levels, and well-being measured by the Problem Areas In Diabetes scale (PAID) and the mental component summary score, SF12 (SF12, mcs). Intention-to-treat analyses were performed. Predefined subgroups analyses were performed. Results The differences between the intervention- and the control practices' mean HbA1c and total cholesterol at follow-up adjusted for baseline values and clustering were respectively: -0.02%-points (95% CI: -0.11 to 0.07; p: 0.67); 0.08 mmol/l (95% CI: 0.01 to 0.15; p: 0.02). Differences in median scores adjusted for clustering were for PAID: 1.25; p = 0.31 and SF12, mcs: 0.99; p = 0.15. Women in intervention practices differed from women in usual practices on mean HbA1c: -0.12%-points (-0.23 to -0.02; p = 0.02) and SF12, mcs: 2.6; p = 0.01. Conclusions Offering a training course for general practice nurses in applying the Self-determination theory in current type 2 diabetes care had no effect compared with usual practice measured by HbA1c and total cholesterol levels and the well-being at 18 months of follow-up in a comprehensive register-based diabetes population. Subgroup analyses suggested a possible effect in women, which deserves further attention. Trial registration ClinicalTrials.gov (Identifier NCT01187069).